MANAJEMEN PEMBELAJARAN DARING PADA PROGRAM TAHFIZH AL-QUR’AN DI MASA KENORMALAN BARU DI AL-WAFI ISLAMIC BOARDING SCHOOL DEPOK JAWA BARAT - Yusuf Abdullah (Universitas Islam Depok, 2023)
This study aims to determine the management of courageous learning in the tahfizh Al-Qur'an program at Al-Wafi Islamic Boarding School in the new normal. This research uses an approach approach because it is considered to directly analyze the reality in the field. This research also uses a case study approach to further analyze the findings in the field. After knowing the learning management model, the researcher analyzed the learning effectiveness. The results of this study are; First, courageous learning management in the tahfizh Al-Qur'an program at Al-Wafi Islamic Boarding School in the new normal period in the form of lesson planning, implementation of learning, and evaluation of learning. Second, the effectiveness of the bold learning process in the tahfizh Al-Qur'an program at the Al-Wafi Islamic Boarding School in the new normal can be seen from two things, the effectiveness of bold learning compared to conventional learning and the effectiveness of using bold application methods and media